2013
DOI: 10.1111/den.12158
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of double‐guidewire technique for difficult biliary cannulation in endoscopic retrograde cholangiopancreatography

Abstract: DGT may replace SGT or become the salvage procedure in cases of unsuccessful SGT as a result of its high success rate with an acceptable incidence of PEP. Failed pancreatic duct stenting in these techniques was frequently associated with PEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…It stabilizes the papilla, closes the pancreatic duct and guides the second guidewire into the biliary axis by straightening the axis. 15,22,23 Other studies showed a success rate of 80-90% 13,14,16,20 at least equal to the pre-cut techniques. The DGW technique allows catheterization of the CBD in 45-90% of patients after failure of the standard technique.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It stabilizes the papilla, closes the pancreatic duct and guides the second guidewire into the biliary axis by straightening the axis. 15,22,23 Other studies showed a success rate of 80-90% 13,14,16,20 at least equal to the pre-cut techniques. The DGW technique allows catheterization of the CBD in 45-90% of patients after failure of the standard technique.…”
Section: Discussionmentioning
confidence: 94%
“…Pre-cut techniques allow access to the CBD but can significantly increase the risk of complications: acute pancreatitis, perforation and hemorrhage. 15,16 It seems that a sequential and standardized approach would increase successful CBD access rates and reduce complications especially for difficult biliary cannulation. DGW technique was not superior when compared to pre-cut or cannulation techniques with a conventional guidewire, and the risk of acute pancreatitis was increased.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that PGW technique increased PEP in difficult cannulation cases . On the other hand, some studies suggested that PGW technique did not increase PEP . However, SOD is excluded in the report of Xinopoulos et al In the group limited to SOD there are few papers confirming that PGW technique is a risk for PEP.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to standard cannulation, DWT may replace standard cannulation or become the salvage procedure in cases of unsuccessful biliary cannulation as a result of its high success rate with an acceptable incidence of PEP . For patients with periampullary duodenal diverticulum, DWT may offer a safe and effective method in biliary cannulation compared to TPS …”
Section: Discussionmentioning
confidence: 99%